Memo1 gene expression in kidney and bone is unaffected by dietary mineral load and calciotropic hormones - Matthias B. Moor; Olivier Bonny (Physiological Reports, 2020)
Abstract Mediator of cell motility 1 (MEMO1) is a ubiquitously expressed modulator of cellular responses to growth factors including FGF23 signaling, and Memo1‐deficient mice share some phenotypic traits with Fgf23‐ or Klotho‐deficient mouse models. Here, we tested whether Memo1 gene expression is regulated by calciotropic hormones or by changing the dietary mineral load. MLO‐Y4 osteocyte‐like cells were cultured and treated with 1,25(OH)2‐vitamin D3. Wild‐type C57BL/6N mice underwent treatments with 1,25(OH)2‐vitamin D3, parathyroid hormone, 17β‐estradiol or vehicle. Other cohorts of C57BL/6N mice were fed diets varying in calcium or phosphate content. Expression of Memo1 and control genes was assessed by qPCR. 1,25(OH)2‐vitamin D3 caused an acute decrease in Memo1 transcript levels in vitro, but not in vivo. None of the hormones tested had an influence on Memo1 transcripts, whereas the assessed control genes reacted the expected way. Dietary interventions with calcium and phosphate did not affect Memo1 transcripts but altered the chosen control genes’ expression. We observed that Memo1 was not regulated by calciotropic hormones or change in mineral load, suggesting major differences between the regulation and physiological roles of Klotho, Fgf23, and Memo1.